The effect of different starters on performance and physiological characteristics of early-weaned female Holstein calves - Stipo Benak; Tina Bobić; Zvonimir Steiner; Mario Ronta; Josip Novoselec; Mislav Đidara; Pero Mijić; Vesna Gantner (Mljekarstvo)
The objective of this research was to determine the effect of different starters consisted of dried whey and soy proteins with low anti-nutritive factors (ANFs) + amino acids (lysine and methionine) on body measurements, biochemical parameters, and feed consumption of early-weaned female Holstein calves. Based on the starter, calves were divided into four groups: i) control (control starter), ii) E1 (starter with added dry whey), iii) E2 (starter with added soy proteins with low ANFs + lysine and methionine), and iv) E3 (starter with added dry whey and soy proteins with low ANFs + lysine and methionine). Results indicate that different starters based on whey powder and soy proteins with low ANFs + lysine and methionine significantly affected the consumption of milk replacer and starter, the total consumption of dry matter, then withers in height, and body length (among body traits) as well as NEFA (among blood biochemical parameters) of female Holstein calves. Finally, starters based on dried whey and soy proteins with low ANFs + lysine and methionine could be recommended to optimize the growth and feed consumption.